Adenosine modulates LPS-induced cytokine production in porcine monocytes - Ondrackova, Petra; Kovaru, Hana; Kovaru, Frantisek; Leva, Lenka; Faldyna, Martin (Cytokine, 2013)
Adenosine plays an important role during inflammation, particularly through modulation of monocyte function. The objective of the present study was to evaluate the effect of synthetic adenosine analogs on cytokine production by porcine monocytes. The LPS-stimulated cytokine production was measured by flow cytometry and quantitative real-time PCR. Adenosine receptor expression was measured by quantitative real-time PCR. The present study demonstrates that adenosine analog N-ethylcarboxyamidoadenosine (NECA) down-regulates TNF-α production and up-regulates IL-8 production by LPS-stimulated porcine monocytes. The effect was more pronounced in CD163(-) subset of monocytes compared to the CD163(+) subset. Although both monocyte subsets express mRNA for A1, A2A, A2B and A3 adenosine receptors, the treatment of monocytes with various adenosine receptor agonists and antagonists proved that the effect of adenosine is mediated preferentially via A2A adenosine receptor. Moreover, the study suggests that the effect of NECA on porcine monocytes alters the levels of the cytokines which could play a role in the differentiation of naive T cells into Th17 cells. The results suggest that adenosine plays an important role in modulation of cytokine production by porcine monocytes.
Keywords: Purinergic P1 Receptor Antagonists; Antigens, CD; antigen CD163; CD antigeny; Adenosine; messenger RNA; purinergní receptory P1; Sus scrofa; lipopolysacharidy; Adenosine-5'-(N-ethylcarboxamide); regulace genové exprese; cytokiny; Lipopolysaccharides; CD163 Antigen; zvířata; antagonisté purinergního receptoru P1; receptory buněčného povrchu; RNA, Messenger; Gene Expression Regulation; Receptors, Cell Surface; Receptors, Purinergic P1; adenosin-5'-(N-ethylkarboxamid); Cytokines; Monocytes; antigeny diferenciační myelomonocytární; Purinergic P1 Receptor Agonists; monocyty; Animals; agonisté purinergních receptorů P1; Antigens, Differentiation, Myelomonocytic; adenosin